Veteran's Village, 1946 - Unidentified photographer (Colorado State University. Libraries, 1946)
A temporary housing structure built at Veteran's Village on CSU's campus, 1946.
Not digitized by CSUL Digital Services.
Keywords: veterans; trailer; temporary housing; military; GI Bill